On the Q-switched operation of Titanium:Sapphire lasers using a graphene-based saturable absorber mirror. (September 2015) - Weigand, R.; Pinto, T.; Crespo, H.M.; Guerra, J.M.
Abstract: We numerically demonstrate Q-switched operation of Titanium:Sapphire lasers using mono and multilayer graphene, deposited on a totally reflecting end mirror as a saturable absorber. Output energies, pulse duration and repetition frequencies of the Q-switched pulse trains are given as a function of the pump intensity for different number of graphene layers and cavity lengths. For the geometries studied, pulses from 17 to 491 ns can be achieved, with energies ranging from 11 to 74 μJ and repetition rates from 0.06 to 2.5 MHz. These results can be useful for designing and building laser cavities for Q-switched and mode-locked operation in laser media with short lifetimes as Titanium:Sapphire. Abstract : Highlights: Numerical demonstration of Q-switch in Ti:Sapphire lasers using graphene. Pulse characteristics given for several cavity lengths and graphene layers. Results relevant for Q-switched and mode-locked lasers with short lifetimes.